2014
DOI: 10.1093/jrr/rru070
|View full text |Cite
|
Sign up to set email alerts
|

Dose- and time-dependent gene expression alterations in prostate and colon cancer cells after in vitro exposure to carbon ion and X-irradiation

Abstract: Hadrontherapy is an advanced form of radiotherapy that uses beams of charged particles (such as protons and carbon ions). Compared with conventional radiotherapy, the main advantages of carbon ion therapy are the precise absorbed dose localization, along with an increased relative biological effectiveness (RBE). This high ballistic accuracy of particle beams deposits the maximal dose to the tumor, while damage to the surrounding healthy tissue is limited. Currently, hadrontherapy is being used for the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 46 publications
4
36
0
Order By: Relevance
“…In a next step, we further investigated the changes of genes involved in motility processes. Our results showed that the magnitude of expression of these genes was time- and dose-dependent for both PC3 and Caco-2 cells, although a cell-type-specific response to X- and carbon ion irradiation was observed ( 29 ). With regard to the changes in cell cycle-related gene sets, we further aimed to investigate the acute cellular responses induced by different radiation qualities.…”
Section: Introductionmentioning
confidence: 72%
“…In a next step, we further investigated the changes of genes involved in motility processes. Our results showed that the magnitude of expression of these genes was time- and dose-dependent for both PC3 and Caco-2 cells, although a cell-type-specific response to X- and carbon ion irradiation was observed ( 29 ). With regard to the changes in cell cycle-related gene sets, we further aimed to investigate the acute cellular responses induced by different radiation qualities.…”
Section: Introductionmentioning
confidence: 72%
“…In addition to anchorage-dependent signaling and morphologic changes adherent cells undergo during detachment, enzymatic detachment solutions, such as trypsin, cleave membrane-bound adhesion molecules that function as major signalers in cellular stress responses, including apoptosis 26 27 28 29 . Post-irradiation cell detachment can further confound determination of RBE because photons and ions have different effects on cell adhesion and motility 30 31 32 . As such, immediate post-irradiation plating readouts involve coupling the effect of the radiation treatment with cellular reattachment, except in the plating efficiency control used to determine overall SF levels.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, carbon ions have a higher RBE and thus greater cell killing effectiveness (19,20). This can overcome radioresistance of hypoxic tumor regions, reduce the effect of fractionation and decrease cell cycle dependence of the radiation response (21).…”
Section: Introductionmentioning
confidence: 99%